2002
DOI: 10.1080/02699050110119844
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle collision factors influence severity and type of TBI

Abstract: Primary objective: To analyse the relationship between motor vehicle collision factors and TBI. Research design: Retrospective design analysed the difference between the types of brain injuries sustained in distinct collision configurations. Methods and procedures: Medical charts and police accident reports were reviewed for individuals sustaining TBI in 168 motor vehicle collisions between 1985± 1998. Main outcomes and results: Lateral collisions and collisions involving contact with a fixed object were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A study using data from the National Health Interview Survey reported increased risk among males and individuals 15 to 24 years of age (Sosin et al, 1996). The use of motor vehicle restraints has been associated with lower incidence and less severe TBI (Hillary et al, 2002), and lack of helmet use has been associated with increased risk of TBI among motorcyclists (Gabella, Reiner, Hoffman, Cook, & Stallones, 1995). Alcohol use has been shown to increase the risk of death in traffic collisions (Cummings, Rivara, Olson, & Smith, 2006), and exacerbate the severity of TBI from motor vehicle crashes (Cunningham et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study using data from the National Health Interview Survey reported increased risk among males and individuals 15 to 24 years of age (Sosin et al, 1996). The use of motor vehicle restraints has been associated with lower incidence and less severe TBI (Hillary et al, 2002), and lack of helmet use has been associated with increased risk of TBI among motorcyclists (Gabella, Reiner, Hoffman, Cook, & Stallones, 1995). Alcohol use has been shown to increase the risk of death in traffic collisions (Cummings, Rivara, Olson, & Smith, 2006), and exacerbate the severity of TBI from motor vehicle crashes (Cunningham et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated hospitalizations, death, and disability related to TBI (McGarry et al, 2002;Schootman et al, 2003;Selassie et al, 2008;Sosin et al, 1996;Thompson et al, 2008;. However, research studies have not typically focused specifically on TBI among all motor vehicle-related traffic incidents (Coben, Steiner, & Miller, 2007;Cunningham, Maio, Hill, & Zink, 2002;Hillary et al, 2002;Viano et al, 1997), and populationbased research on this topic is relatively rare (Javouhey, Guerin, & Chiron, 2006). Therefore, the goal of this population-based study was to describe demographic and incident characteristics of motor vehicle-related TBI and the impact of motor vehicle-related TBI on inpatient hospital resource utilization in Ohio for 2003 through 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Almost universally, medial PFC (MedPFC) and posterior cingulate cortex (PCC) have been identified as central to the network organized around "internal-states" Zou et al, 2009). In addition, because TBI most commonly disrupts frontal systems (and therefore, executive control processes) (Hillary et al, 2002;Whyte et al, 1998), we also aimed to examine fluctuation in the BOLD signal in regions believed to be directly involved in cognitive control and volitional behavior. Thus, we examined resting connectivity in dorsolateral prefrontal cortex (DLPFC) and anterior cingulate cortex (ACC) and related regions during rest that might be best conceptualized as a "goal directed" network.…”
Section: Fmri Wm Paradigm and Off-task Blocksmentioning
confidence: 99%
“…Motor vehicle collisions have the potential to cause a wide variety of acute injuries including traumatic brain injury. 1 With evidence of head trauma, non-reactive pupils have long been observed as a strong predictor of both neurological injury and mortality. [2][3][4] Emergency lateral canthotomy and cantholysis to relieve intraocular pressure following severe motor vehicle collision Jason L Elzinga, Herman Bami Faculty Reviewer: Robert Leeper, MD, FRCSC, FACS (Department of Surgery, Division of General Surgery)…”
Section: Discussionmentioning
confidence: 99%